Case Report: A novel germline donor splicing site mutation of RB1 gene in a Chinese Tibetan pedigree with familial retinoblastoma - He, Guo-qian; Zheng, Ying-chun; Tan, Lin-jun; Shen, Cheng-qi; Gao, Ju; Xiong, Fu; Guo, Xia (Frontiers in Oncology, 2025)
Retinoblastoma (RB) is the most common primary intraocular malignancy in children and mostly initiates with biallelic inactivation of the RB1 gene. Hereditary retinoblastoma accounts for 40% of all cases, with only 6%–10% of patients having a positive family history. The proband, a Chinese Tibetan boy, was diagnosed with RB for leukocoria. The RB1 gene mutations were screened due to disease recurrence. A novel germline donor splicing site mutation (c.861 + 2T>A) from his father was identified by Sanger sequencing and a novel somatic duplication mutation in exon 2 221-224 (p.W75Cfs*36) by next-generation sequencing (NGS). The proband’s younger brother manifested bilateral RB and also carried the same germline mutation. To further explore the possible pathogenicity of the novel germline RB1 mutation (c.861 + 2T>A) in RB development, mutation analysis, bioinformatics analysis, and immunohistochemistry were performed. After RB1 cDNA was amplified, the abnormal script was found to be smaller than the normal script. Compared with normal samples, Sanger sequencing revealed a deletion of 143 bp in the abnormal script. In comparison to healthy individuals, patients exhibited a reduction in the mRNA expression levels of the RB1 gene. The three-dimensional structure predicted by iterative threading assembly refinement (I-TASSER) indicates significant changes in the spatial structure of abnormal proteins after mutation. No expression of RB1 was found in tumor tissue by immunohistochemistry evaluation. Therefore, the novel germline donor splicing site mutation (c.861 + 2T>A) has been confirmed to be a pathological mutation.